Does Finland need an entry-ban system for football matches (and similar public events)? Examining the current state of regulation and security issues. Issue 4 (October 2017) - Paasonen, Jyri; Aaltonen, Mikko
Abstract The need to establish an official entry-ban system has been discussed in the recent years in Finland, as concerns about security risks and spectator violence have been raised particularly in the context of football. However, we do not know much about the level and development of security risks in sporting events in Finland. The purpose of this article is twofold. First, we describe the relevant Finnish legislation governing security in public events, and assess whether an entry-ban system would complement the current regulation in terms of improving security. Second, we present empirical results on the development of security risks in Finnish professional football league (Veikkausliiga), and examine whether there are systematic differences in the occurrence of disturbances in football matches. The primary empirical analysis is based on security reports from Veikkausliiga matches from two seasons (n =396). In addition, we present survey results on how sporting club authorities perceive the need for an entry-ban system, and how the incidence of crowd trouble in football compare with other sports. The results show that the both incidence of crowd trouble and support for an entry-ban system is highest in football, whereas disturbances have also become more common in the recent years. The multivariate analysis suggests that the numbers of home and away fans are the strongest predictors of disturbances. We conclude by discussing the potential benefits and pitfalls of an entry-ban system.